TRANSFORMASI DIGITAL KOMUNITAS SENI: PENGUATAN PORTOFOLIO PELATIH AYODYA PALA MELALUI OPTIMALISASI MEDIA SOSIAL - Costa, Rizky Oktarina (Gapenas Publisher, 2025)
The digital transformation has reshaped the global communication landscape, including the preservation of traditional cultural arts. In response to this dynamic change, a community service program was designed to enhance the capacity of trainers at Sanggar Tari dan Seni Tradisional Ayodya Pala in developing effective and professional digital portfolios. This activity represents the implementation of the Tri Dharma of Higher Education, aimed at empowering arts communities to navigate the digital era, with a focus on strengthening digital literacy, building authentic professional identities, and optimizing social media as a creative platform. The training program was systematically structured based on the Guidebook for Effective and Professional Digital Portfolios, covering key topics such as the importance of digital portfolios, strategies for targeting audiences, selecting appropriate social media platforms, content management techniques, interactive promotion, and digital performance analysis. Participants were also equipped with technical skills to develop dynamic visual content, including short videos and Instagram Reels, to creatively and professionally increase audience engagement. Evaluation results from pre-tests and post-tests showed that 92% of participants found the material relevant to their practical needs, and 85% committed to implementing the digital content management strategies learned. Furthermore, there was a 41% improvement in participants' understanding of the basic concepts of personal branding on social media. These findings demonstrate that the training successfully fostered critical awareness regarding the importance of professional presence in digital spaces and participants’ readiness to adopt adaptive communication strategies. This program not only strengthened the digital competitiveness of the Ayodya Pala community but also enriched the academic experience of students involved in facilitating the activities. The success of the program highlights that integrating digital literacy with cultural preservation is a strategic effort to ensure the sustainability of traditional arts amid globalization. It is hoped that through further mentoring and continuous skill development, traditional arts communities will increasingly strengthen their existence as adaptive cultural communicators in the modern era.